1881 Ill. Laws 71, § 2 - (:unkn) unknown (My University, 1881)
Prohibited selling, giving, loaning, hiring for barter any minor a pistol, revolver, derringer, Bowie knife, dirk or other deadly weapon. Punishable by fine of $25-200.
Keywords: TRANSFER - MINORS